Comparative reliability assessment of a solid, box and I-section Nigerian-grown African birch (Anogeissus leiocarpus) timber column. (2nd January 2021) - Wilson, U.N.; Adedeji, A.A.; Alomaja, J.A.; Sani, J.E.; Babatunde, O.A.; Abubakar, P.
ABSTRACT: A structural reliability analysis was carried out on the Nigerian-grown African birch timber to ascertain its performance as a structural timber column for solid, box and I built-up sections using FORTRAN language. By varying its depth, length and the axial load supported by the column, results obtained reveal that the timber is adequate for use as solid timber column at a depth and breadth of 150 mm, an effective height of 3600 mm and an axial load of 260 kN with its probability of failure as 8.85 × 10 −3 . The corresponding I-section was found to be unsafe, whereas the box-section supported the design load with a probability of failure of 1.6 × 10 −6 . For the design dimension (150 × 150 mm), the solid section has a compressive capacity twice that of the I-section. The box-section has a capacity three times that of the I-section and twice that of the solid section at increased loads.